2020
DOI: 10.3174/ajnr.a6784
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT-Guided Core Needle Biopsies of Head and Neck Masses: Technique, Histopathologic Yield, and Safety at a Single Academic Institution

Abstract: BACKGROUND AND PURPOSE: CT-guided head and neck biopsies can be challenging due to the anatomy and adjacent critical structures but can often obviate the need for open biopsy. A few studies and review articles have described approaches to biopsy in the head and neck. This retrospective study evaluated technical considerations, histopathologic yield, and safety in CT-guided head and neck core needle biopsies. MATERIALS AND METHODS:A retrospective review of head and neck biopsies performed from January 2013 thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The minor complication rate was 12.5% (2/16), including mild inflammation of the puncture site and self-limited blood-tinged sputum. Mild infection and bleeding were the most reported minor complications after image-guided biopsy in the H&N. [3][4][5][6][7][8][9][10][11] Other minor complications included vasovagal reaction, transient facial palsy, and CSF leakage, which did not occur in this study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The minor complication rate was 12.5% (2/16), including mild inflammation of the puncture site and self-limited blood-tinged sputum. Mild infection and bleeding were the most reported minor complications after image-guided biopsy in the H&N. [3][4][5][6][7][8][9][10][11] Other minor complications included vasovagal reaction, transient facial palsy, and CSF leakage, which did not occur in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown a diagnostic rate of CT-guided core needle biopsy of 73%-96.8% in lesions involving the H&N as a whole. [4][5][6][7] The average size of all target lesions was approximately 2.4-3.3 cm, 4-6 including superficial and lower cervical masses. For emerging infrared navigation-guided biopsy, the diagnostic rate was approximately 90%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Several standard approaches to H&N CT-guided CNB are used, including subzygomatic, paramaxillary, retromandibular, anterior, lateral, and posterior approaches. [7][8][9][10][11][12][13] These are illustrated in Fig 1 . A recently published review of 27 CT-guided CNBs by Hillen et al 14 demonstrated the effectiveness and safety of these procedures for H&N lesions. However, large studies evaluating the diagnostic yield and safety profile of CT-guided H&N CNBs with a variety of locations and lesion sizes are lacking.…”
mentioning
confidence: 99%